Developing of Audio Visual Text Module on Congratulation and Compliment Expressions - Febrika Meylani Irwanda Putri; Erwin Ashari; Albert Efendi Pohan; Warno Edi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
Learning media is an important component in learning. One of the media that can be used is audio visual media. The aim of this study was to develop a feasible Audio Visual Text Module on Congratulation and Compliment Expressions as learning media.This reasearch was conducted at Karang Taruna RW 17 English Course Sei Langkai, Batam, and research and development (R&D)Hannafin and Peck modelwas used. The instrument used to collect data in this research wasquestionnaireswhich validated by material and media experts, then shared to tutors and studentsusing a Likert scale. Product trial obtained 77.02% for students response and it was categorized as ‘agree’ category. Meanwhile it obtained 76.67% for tutor rensponse and it was categorized as ‘agree’ category.Usage trial obtained 87.07% for students response and it was categorized as ‘strongly agree’ category. Meanwhile it obtained 88.66 for tutor rensponse and it was categorized as ‘strongly agree’ category. The products of this research are module and audio visual (MP4) about Congratulating and Compliment Expressions, and both are neccessary to be used as learning media.